2012
DOI: 10.1111/j.1600-0625.2012.01462.x
|View full text |Cite
|
Sign up to set email alerts
|

MiR‐21 is up‐regulated in psoriasis and suppresses T cell apoptosis

Abstract: :  MicroRNAs are short non‐coding RNAs that regulate gene expression. Previously, in a genome‐wide screen, we found deregulation of microRNA expression in psoriasis skin. MicroRNA‐21 (miR‐21) is one of the microRNAs significantly up‐regulated in psoriasis skin lesions. To identify the cell type responsible for the increased miR‐21 level, we compared expression of miR‐21 in epidermal cells and dermal T cells between psoriasis and healthy skin and found elevated levels of miR‐21 in psoriasis in both cell types. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
130
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 153 publications
(136 citation statements)
references
References 26 publications
5
130
0
1
Order By: Relevance
“…In recent years, with the comprehensive genetic analysis on miR, increasing numbers of specific miR have been discovered to be related with the pathology of psoriasis 19, including miR‐21 20, miR‐146a 21, miR‐424 22 and miR‐99a 23. Other previous studies have also shown that miR‐203, miR‐125b, miR‐99a and miR‐197 were relevant to the pathogenesis of psoriasis by regulating target genes 24, 25, 26, 27.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, with the comprehensive genetic analysis on miR, increasing numbers of specific miR have been discovered to be related with the pathology of psoriasis 19, including miR‐21 20, miR‐146a 21, miR‐424 22 and miR‐99a 23. Other previous studies have also shown that miR‐203, miR‐125b, miR‐99a and miR‐197 were relevant to the pathogenesis of psoriasis by regulating target genes 24, 25, 26, 27.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, splenocyte suspensions were generated from MOG (27). Increased miR-21 levels have also been reported in T cells from patients with SLE and psoriasis (28)(29)(30), and these levels correlated with disease activity. Given the ameliorating effect of anti-miR-21 we observed in EAE, the implication of miR-21 in multiple autoimmune disease models, and the expression profile of miR-21 in patients with MS and other autoimmune diseases, silencing miR-21 may be an effective therapeutic approach in the treatment of MS and other Th17-mediated inflammatory diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Increased expression of miR-21 has been observed in human autoimmune conditions including MS, systemic lupus erythematosus (SLE), and psoriasis (27)(28)(29)(30). However, the role of miR-21 and its intrinsic requirement in Th cell differentiation and autoimmunity remains unclear.…”
Section: Mir-21 Promotes Th17 Differentiation Cd4mentioning
confidence: 99%
“…Often a miRNA has hundreds of different target genes, regulating biological functions through the modulation of their expression (9,10). Several miRNAs have been identified to have important and specific functions in the skin, both in keratinocytes (11)(12)(13)(14)(15)(16) and in other cell types (17,18), showing the relevance of this class of molecules in skin biology.…”
Section: Introductionmentioning
confidence: 99%